Protein Aggregation and Disaggregation in Cells and Development. Issue 21 (15th October 2021) - Fassler, Jan S.; Skuodas, Sydney; Weeks, Daniel L.; Phillips, Bryan T.
Graphical abstract: Highlights: Regulated aggregation affects protein storage, activity and spatial distribution. Many "bodies" historically connected to cell and development are protein condensates. Physiological aggregates are regulated, reversible, and often multifunctional. Chaperones, protein modification, local milieu and co-aggregates alter aggregation. Exploring multiple experimental systems helps identify regulators of aggregation. Abstract: Protein aggregation is a feature of numerous neurodegenerative diseases. However, regulated, often reversible, formation of protein aggregates, also known as condensates, helps control a wide range of cellular activities including stress response, gene expression, memory, cell development and differentiation. This review presents examples of aggregates found in biological systems, how they are used, and cellular strategies that control aggregation and disaggregation. We include features of the aggregating proteins themselves, environmental factors, co-aggregates, post-translational modifications and well-known aggregation-directed activities that influence their formation, material state, stability and dissolution. We highlight the emerging roles of biomolecular condensates in early animal development, and disaggregation processing proteins that have recently been shown to play key roles in gametogenesis and embryogenesis.